Kecerdasan Emosi, Anonimitas dan Cyberbullying (Bully Dunia Maya) - Nirwana Sari, Renny; ., Suryanto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
The purpose of this study to examine the relationship between emotionalintelligence and anonymity with cyberbullying in terms of gender. This study was donewith quantitative methods. Measurement variables of this research using a scale ofcyberbullying, emotional intelligence scale and the scale of anonymity. were Subjectsjunior high school students in Sidoarjo, which amounted to 44 students with a lifespan of13-17 years with a mix of men and women at least 21 of 23 students, which is inaccordance with the criteria as perpetrators of cyberbullying. were analyzed usingregression analysis, partial correlation,and Anova. The results showed: first, there wasno significant relationship between emotional intelligence and anonymity withcyberbullying. second, there is a positive relationship of emotional intelligence withcyberbullying. Third, the anonymity has a negative relationship with cyberbullying.Fourth, the difference in cyberbullying behavior between men and women, where menthere is a tendency to become perpetrators of cyberbullying.Keywords : Emotional Intelligence , Anonymity , Cyberbullying